Structural Analysis of Pyramids: Insights from the Giza 3D Survey Project - Kawae, Yukinori (Universitas Negeri Surabaya, 2024)
Within the Memphis region of Egypt, the Old Kingdom period (approximately 2686–2181 BCE) saw the construction of over 70 pyramids. The extant survey data for these pyramids, derived mainly from architectural studies, have not been substantially updated. The information from this period predominantly encompasses descriptive accounts and schematic representations, focusing on the dimensions, internal chambers, and passageways of the pyramids. Notably absent are detailed documentations that provide insights into the individual stone blocks and the intricacies of their masonry. Consequently, the current understanding of the pyramid construction methodologies of this era remains largely hypothetical. Since 2005, I have been actively engaged in an interdisciplinary 3D survey initiative, focusing on acquiring laser- scanned 3D data of Memphite pyramids. This endeavor aims to analyze their structural forms to elucidate the progression in construction techniques during this epoch. Beginning in 2013, the “Giza 3D Survey” project was initiated as a collaboration between academia and industry. This project sought to comprehensively update the exterior measurement data of the Giza pyramid complex, employing “Structure from Motion/Multi-View Stereo (SfM/MVS)” technologies to generate 3D representations from photographic imagery. This comprehensive approach seeks to unravel the construction methodologies of these ancient structures. As a result of a decade-long survey, it has been discovered that the pyramids of Giza are not merely accumulations of limestone blocks. Instead, they contain a central “core structure” in a step-like formation, a framework made up of “backing stones,” and areas filled with debris and sand, referred to as “chamber method.”